Comparison of outcomes between laparoscopic and open pancreaticoduodenectomy without radical lymphadenectomy: Results of coarsened exact matching analysis using national database systems. Issue 1 (16th May 2021) - Nakata, Kohei; Yamamoto, Hiroyuki; Miyata, Hiroaki; Kakeji, Yoshihiro; Kitagawa, Yuko; Nakamura, Masafumi
Abstract: Introduction: Laparoscopic pancreaticoduodenectomy has recently been covered under Japan's insurance system for patients not requiring lymph node dissection. Only high‐volume hospitals that meet specific criteria are permitted to perform laparoscopic pancreaticoduodenectomy. Although open and laparoscopic pancreaticoduodenectomy outcomes with lymph node dissection have been described previously, procedures performed without lymph node dissection have not been compared using a nationwide database. This study aimed to review the results of laparoscopic pancreaticoduodenectomy and compare them to those of open pancreaticoduodenectomy (OPD) using records from a nationwide database. Methods: We collected patient demographic and medical data of 2900 patients who underwent pancreaticoduodenectomy (laparoscopic, n = 162; open, n = 2738) without lymph node dissection between 2016 and 2018 from the National Clinical Database in Japan. Coarsened exact matching was used to match patients in the laparoscopic and open pancreaticoduodenectomy groups. Results: In‐hospital mortality was not observed in the laparoscopic pancreaticoduodenectomy group. The rate of conversion to an open procedure was 6.8% (11 cases). After 1:1 matching, we obtained 141 pairs of patients for comparison. The mortality rate was comparable in the laparoscopic and open pancreaticoduodenectomy groups (0.0% vs 0.7%, respectively; P = 1.00). The laparoscopic approach showed more favorable results in terms of median blood loss. Postoperative pancreatic fistula formation and complications were comparable between the two groups. Conclusions: Our results indicate that laparoscopic pancreaticoduodenectomy could be introduced successfully, and the outcomes achieved by the institutions included in our study were comparable to those of open pancreaticoduodenectomy.